LINC00852 promotes the proliferation and invasion of ovarian cancer cells by competitively binding with miR-140-3p to regulate AGTR1 expression - Zhi-wei Qiao; Ying Jiang; Ling Wang; Lei Wang; Jing Jiang; Jing-ru Zhang; Peng Mu (BMC Cancer, 2021)
Abstract Background Dysregulation of long non-coding RNAs (lncRNAs) has been identified in ovarian cancer. However, the expression and biological functions of LINC00852 in ovarian cancer are not understood. Methods The expressions of LINC00852, miR-140-3p and AGTR1 mRNA in ovarian cancer tissues and cells were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR) assay. Gain- and loss-of-function assays were performed to explore the biological functions of LINC00852 and miR-140-3p in the progression of ovarian cancer in vitro. The bindings between LINC00852 and miR-140-3p were confirmed by luciferase reporter gene assay, RNA immunoprecipitation (RIP) assay and RNA pull-down assay. Results We found that LINC00852 expression was significantly up-regulated in ovarian cancer tissues and cells, whereas miR-140-3p expression was significantly down-regulated in ovarian cancer tissues. Functionally, LINC00852 knockdown inhibited the viability, proliferation and invasion of ovarian cancer cells, and promoted the apoptosis of ovarian cancer cells. Further investigation showed that LINC00852 interacted with miR-140-3p, and miR-140-3p overexpression suppressed the viability, proliferation and invasion of ovarian cancer cells. In addition, miR-140-3p interacted with AGTR1 and negatively regulated its level in ovarian cancer cells. Mechanistically, we found that LINC00852 acted as a ceRNA of miR-140-3p to promote AGTR1 expression and activate MEK/ERK/STAT3 pathway. Finally, LINC00852 knockdown inhibited the growth and invasion ovarian cancer in vivo. Conclusion LINC00852/miR-140-3p/AGTR1 is an important pathway to promote the proliferation and invasion of ovarian cancer.